Quality indicators, reintroduction of oral feeding and the management of speech and language therapist in ICU (Research, Society and Development, 2021)
Aims: To quantify the results indicators of the Speech-Language Pathology Team of the Intensive Care Unit (ICU). Methods: A observational, transversal, quantitative, descriptive, retrospective research. Was included the records of the books of the Speech-Language Pathology team inserted in the ICU university hospital. Age, sex, main reason for ICU admission, presence of orotracheal intubation, presence of tracheostomy, presence of alternative feeding tube, type of speech therapy performed and type of diet released / Offered. The scope considered in the research was the biennium 2014-2016. The scale used to determine the degree of dysphagia was drawn by the American Speech-Language-Hearing Association, (ASHA NOMS). The time for reintroduction of oral feeding was determined from the subtraction between the beginning of Speech-Language Therapy and the beginning of oral feeding for the same period. Inclusion criteria: patients with at least 3 sequential speech therapy visits; Oral feeding recommended for assessment and / or suitable to initiate the decannulation process; Methodology: incomplete information in the book of records; Deaths during the stay in a ICU. Results: About 88.3%and 88,9% of the patients had oral re-introduction; alternative feeding methods removed, respectively, during the first five days of hospitalization. Conclusion: The intensive follow-up of Speech Therapy allows interdisciplinarity and integral care of the patient, culminating in less time: hospitalization and percentage of alternative feeding methods.